Method for identifying cast aluminum alloy heat transfer corrosion resistance of anti-freezing solution

Through a method to identify the heat-transfer corrosion properties of antifreeze liquid, the corrosion and crystallization problems caused by the chemical reaction between antifreeze and aluminum alloy are solved, and effective detection and performance improvement of antifreeze liquid are achieved.

CN119413701APending Publication Date: 2025-02-11CHANGZHOU HUANGHAI AUTOMOTIVE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693030.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

During use, existing antifreeze is prone to chemical reaction with aluminum alloy, resulting in corrosion and crystallization, and seriously damage the engine.

Method used

A method of identifying the heat-transfer corrosion resistance of antifreeze is used to detect the performance of antifreeze by preparing test pieces, preparing corrosion water and sample, conducting heat-transfer corrosion tests, and calculating heat-transfer corrosion rate.

Benefits of technology

Effectively detect the performance of antifreeze in real situations, avoid batch crystallization failures, reduce the active technical transformation and compensation of car companies, and protect brand reputation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FDA0005151463380000031
    Figure FDA0005151463380000031
Patent Text Reader

Abstract

The invention relates to a method for identifying aluminum alloy heat transfer corrosion resistance of an anti-freezing solution. The method comprises the following steps: S1, preparation work; s2, a test step; s3, performing calculation; the step S1 of preparation work comprises the substeps of S11, preparation of a test piece; s22, sampling is carried out; s33, preparing a test solution; the step (S33) of preparing the test solution comprises the substeps of (S111) preparing corrosion water and (S222) preparing a sample; s222, preparation of the sample comprises the following steps: S1111, preparation of an engine coolant concentrated solution sample; s2222, preparing an engine cooling liquid sample; and S3333, preparing a cooling liquid sample containing potassium fluoroaluminate. According to the method for identifying the aluminum alloy heat transfer corrosion resistance of the anti-freezing solution, the real use performance of the anti-freezing solution can be effectively detected, the occurrence of batch crystallization faults is avoided, and batch active technical improvement on vehicle enterprises is avoided, so that a large amount of compensation and brand reputation are retrieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of identifying the heat transfer corrosion resistance of antifreeze to cast aluminum alloy, in particular to a method for identifying the heat transfer corrosion resistance of antifreeze to aluminum alloy. Background Art

[0002] With the continuous progress of society, the automobile industry has developed rapidly. There are many components in a car, and engine coolant is an important component. Usually, after the production of coolant, it needs to be tested for the heat transfer corrosion resistance of cast aluminum alloy. At present, the SH / T 0620-1995 engine coolant to cast aluminum total corrosion determination method under heat transfer state has been used for 29 years for the heat transfer corrosion resistance of antifreeze. The radiator manufacturing process has long been changed from the original welded plate radiator to the use of potassium fluoroaluminate as a catalyst and integrated automatic welding; the above structural changes will lead to a small amount of potassium fluoroaluminate residue, and as a catalyst, it will cause a chemical reaction in the antifreeze, which will eventually cause the antifreeze to deteriorate and crystallize, and scale will fill the entire engine waterway, seriously damaging the engine.

[0003] The existing radiator manufacturing method uses spray brazing flux (potassium fluoroaluminate) for automatic welding, which results in the presence of trace amounts of potassium fluoroaluminate in the radiator; D: 2AL(OH)4-=Al2O3+2OH - +3H2O; fluoride ions also interact with the oxide film on the aluminum surface and OH - Similarly, fluoride ions act as nucleophiles to attack the highly charged, small radius Al atoms in Al2O3 crystals. 3+ , weaken Al 3+ With O2 - The electrostatic interaction between them eventually causes the fluoride ions to replace O2 - With Al 3+ Combined with the coordinated complex ion ALF3 and dissolved (equivalent to a catalyst), this complex ion also blocks Al 3+ With O2 - contact between them, promoting O2 - In solution, it reacts with water to convert into OH -And the Al2O3 oxide film will crack. Under the synergistic effect of metal ions, water molecules, and H+ penetrating pores and reacting with aluminum, the oxide film on the aluminum surface will dissolve. As the surface aluminum oxide is dissolved, the Al is exposed to the alkaline environment and reacts, eventually generating aluminum oxide solids, which will pollute the entire antifreeze. 2Al+NaNO2+NaOH+2H2O=2NaAlO2+Na3.H2O (transition stage); 2NaAlO2+2H2O=Al(OH)3+NaOH (final stage); 2Al(OH)3=Al2O3+3H2O (thermal decomposition). The above reaction conditions are constant temperature at 135℃±1℃ and pressure at 190-200kPa for 168h. Summary of the invention

[0004] The technical problem to be solved by the present invention is: in order to solve the problems existing in the above-mentioned background technology, a method for identifying the antifreeze's resistance to heat transfer corrosion of aluminum alloy is provided, which can effectively detect the performance of the antifreeze in real conditions, avoid batch crystallization failures, and cause batch active technical reforms for automobile companies, thereby recovering a large amount of compensation and brand reputation.

[0005] The technical solution adopted by the present invention to solve its technical problem is: a method for identifying the heat transfer corrosion resistance of antifreeze liquid to aluminum alloy, comprising the following steps: S1, preparation; S2, test steps; S3, calculation; the S1, preparation includes S11, preparation of test pieces; S22, sampling; S33, preparation of test solution; the S33, preparation of test solution includes S111, preparation of corrosive water and S222, preparation of test sample; the S222, preparation of test sample includes S1111, preparation of engine coolant concentrate sample; S2222, preparation of engine coolant sample; S3333, preparation of coolant sample containing potassium fluoroaluminate.

[0006] To further illustrate, in the above technical solution, the preparation of the S11 specimen includes S11-1, the specimen is polished with No. 150, No. 180 and No. 240 emery cloth or sandpaper in turn, and then polished with metallographic sandpaper; S11-2, the specimen is first washed with warm water, then rinsed with distilled water, and finally rinsed with anhydrous ethanol; S11-3, the specimen is placed in a vacuum drying oven at 65-90°C and dried for 4 hours, and then picked up with tweezers; S11-4, the picked up specimen is placed in a dryer and cooled to room temperature; S11-5, the specimen is weighed to 0.1 mg using an analytical balance.

[0007] To further illustrate, in the above technical solution, the preparation of S111 and corrosive water is to dissolve 220 mg of sodium chloride in 1 L of distilled water.

[0008] To further illustrate, in the above technical solution, the preparation of the engine coolant concentrate sample in S1111 is to prepare a 25% aqueous solution sample by mixing 1 volume of the engine coolant concentrate sample with 3 volumes of prepared corrosive water.

[0009] To further illustrate, in the above technical solution, the preparation of the engine coolant sample in S2222 is to dilute the coolant with the prepared corrosive water to a 25% aqueous solution sample.

[0010] To further illustrate, in the above technical solution, the S3333, preparing a coolant sample containing potassium fluoroaluminate, is to add potassium fluoroaluminate to a coolant sample with a total volume of 1L.

[0011] Further explanation, in the above technical scheme, the S2 test steps include the first step: thoroughly cleaning the components used in the heat transfer corrosion chamber; the second step: using a new O-shaped rubber sealing ring, adding a small amount of sample into the O-shaped groove before the O-shaped rubber sealing ring is embedded; the third step: adding 500L of sample into the heat transfer corrosion chamber through the air inlet, installing the air filling pipe, installing the safety cover, and gradually pressurizing the heat transfer corrosion chamber to 140kPa with compressed air; turning on the heater, heating the specimen, and gradually adjusting the pressure. When the temperature of the specimen reaches 135°C, the pressure in the heat transfer corrosion chamber is 190-200kPa; the fourth step: controlling the temperature of the specimen at 134-136°C, observing the temperature of the thermometer placed in the thermometer jack of the specimen at regular intervals, and the test continues for one week at this temperature; the fifth step: at the end of the test, turning off the heater, waiting for the heat transfer corrosion chamber to cool to room temperature, releasing the pressure in the heat transfer corrosion chamber, removing the air filling pipe, pouring out or siphoning out the sample, disassembling the heat transfer corrosion chamber, and taking out the specimen; the sixth step: the specimen Cleaning: Wash the specimen with a soft brush and neutral detergent, and use the edge of a plastic scraper to remove the residue of the O-ring on the specimen; in a fume hood, soak the specimen in a mixture of chromium trioxide and phosphoric acid at 80°C for 5 minutes, and occasionally scrub the surface of the specimen with a soft brush; then transfer the beaker containing the specimen's cleaning solution to an ultrasonic cleaner for cleaning for 1 minute; remove the specimen from the cleaning solution, rinse it with tap water, then with distilled water, and finally with anhydrous ethanol; examine the specimen with a microscope If there is any residue on the surface of the test piece, continue to clean it repeatedly; after cleaning, dry the test piece in a vacuum drying oven; use tweezers to pick up the test piece and put it in a dryer to cool it to room temperature, and then weigh it to 0.1 mg; determination of the blank cleaning mass loss value: take three test pieces prepared according to step S22 and weigh them to 0.1 mg, then clean them according to the cleaning of the test piece in step 6 and weigh them to 0.1 mg, and take the average cleaning mass loss value of the three test pieces as the blank cleaning mass loss value.

[0012] Further explanation: In the above technical solution, the S3 is calculated as the heat transfer corrosion rate R (mg / cm 2 ) is calculated according to the following formula:

[0013]

[0014] Where: m1-mass of the specimen before the test, g; m2-mass of the specimen after the test, g; B-mass loss value of the blank cleaning of the specimen, g; A-heat transfer surface area of ​​the specimen in the O-ring, cm 3 .

[0015] The beneficial effect of the present invention is that a method for identifying the heat transfer corrosion resistance of antifreeze against aluminum alloy proposed by the present invention can effectively detect the performance of antifreeze in actual conditions, avoid batch crystallization failures, and cause batch active technical reforms for automobile companies, thereby recovering a large amount of compensation and brand reputation. DETAILED DESCRIPTION

[0016] In the present application, S3333, the coolant sample containing potassium fluoroaluminate needs to be prepared after the molecular content calculation and solution ratio calculation, and the required weight of potassium fluoroaluminate is weighed on a balance and added to the coolant sample. In the present application, the fluoride ion content is preferably 30-60ppm.

[0017] The present application provides a method for identifying the heat transfer corrosion resistance of antifreeze to aluminum alloy, comprising the following steps: S1, preparation; S2, test steps; S3, calculation; S1, preparation includes S11, preparation of test piece; S22, sampling; S33, preparation of test solution; S33, preparation of test solution includes S111, preparation of corrosive water and S222, preparation of test sample; S222, preparation of test sample includes S1111, preparation of engine coolant concentrate sample; S2222, preparation of engine coolant sample; S3333, preparation of coolant sample containing potassium fluoroaluminate.

[0018] Among them, the preparation of S11 specimens includes S11-1, the specimens are polished with 150, 180 and 240 sandpapers in turn, and then polished with metallographic sandpaper; S11-2, the specimens are first washed with warm water, then rinsed with distilled water, and finally rinsed with anhydrous ethanol; S11-3, the specimens are placed in a vacuum drying oven at 65-90℃ for 4 hours and then clamped with tweezers; S11-4, the clamped specimens are placed in a dryer and cooled to room temperature; S11-5, the specimens are weighed to 0.1 mg using an analytical balance. S111, the preparation of corrosion water is to dissolve 220 mg of sodium chloride in 1 L of distilled water. S1111, the preparation of engine coolant concentrate sample is to mix 1 volume of engine coolant concentrate sample with 3 volumes of prepared corrosion water to make a 25% aqueous solution sample. S2222. The preparation of the engine coolant sample is to dilute the coolant with the prepared corrosive water to a 25% aqueous solution sample. S3333. The preparation of the coolant sample containing potassium fluoroaluminate is to add potassium fluoroaluminate to the coolant sample with a total volume of 1L.S2. The test steps include the following: Step 1: thoroughly clean all components used in the heat transfer corrosion chamber; Step 2: use a new O-ring and add a small amount of sample into the O-ring groove before the O-ring is embedded; Step 3: add 500L of sample into the heat transfer corrosion chamber through the air inlet, install the air filling pipe, install the safety cover, and gradually pressurize the heat transfer corrosion chamber to 140kPa with compressed air; turn on the heater to heat the specimen and gradually adjust the pressure. When the specimen temperature reaches 135℃, the pressure in the heat transfer corrosion chamber is 190-200kPa; Step 4: control the temperature of the specimen at 134-136℃, observe the temperature of the thermometer placed in the thermometer jack of the specimen at regular intervals, and continue the test at this temperature for one week; Step 5: at the end of the test, turn off the heater, wait for the heat transfer corrosion chamber to cool to room temperature, release the pressure in the heat transfer corrosion chamber, remove the air filling pipe, pour out or siphon out the sample, disassemble the heat transfer corrosion chamber, and take out the specimen; Step 6: cleaning of the specimen: use a soft brush and Wash the specimen with a neutral detergent, and use the edge of a plastic scraper to remove the residue of the O-ring on the specimen; in a fume hood, soak the specimen in a mixture of chromium trioxide and phosphoric acid at 80°C for 5 minutes, and occasionally scrub the surface of the specimen with a soft brush; then transfer the beaker containing the specimen's cleaning solution to an ultrasonic cleaner for cleaning for 1 minute; remove the specimen from the cleaning solution, rinse it with tap water, then with distilled water, and finally with anhydrous ethanol; check the surface of the specimen with a microscope, and if there is any residue, continue to clean it repeatedly; after cleaning, dry the specimen in a vacuum drying oven; clamp the specimen with tweezers into a dryer and cool it to room temperature, and then weigh it to 0.1 mg; Determination of the blank cleaning mass loss value: take three specimens prepared in step S22 and weigh them to 0.1 mg, then clean and weigh them according to the cleaning of the specimen in step 6 to 0.1 mg, and take the average cleaning mass loss value of the three specimens as the blank cleaning mass loss value. S3 is calculated as the heat transfer corrosion rate R (mg / cm2) of the sample. 2 ) is calculated according to the following formula:

[0019]

[0020] Where: m1-mass of the specimen before the test, g; m2-mass of the specimen after the test, g; B-mass loss value of the blank cleaning of the specimen, g; A-heat transfer surface area of ​​the specimen in the O-ring, cm 3 .

[0021] Compared with the traditional method of identifying the heat transfer corrosion resistance of antifreeze to aluminum alloy, the present application has the following advantages: when conducting the corrosion test of engine coolant on cast aluminum alloy under heat transfer state, a certain amount of fluoride ions is added to ensure whether the antifreeze can maintain stability in the presence of fluoride ions, so as to avoid chemical reactions causing crystallization.

[0022] The above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloys, characterized in that: The method comprises the following steps: S1, preparation work; S2, test steps; S3, calculation; the S1, preparation work comprises S11, preparation of test piece; S22, sampling; S33, preparation of test solution; the S33, preparation of test solution comprises S111, preparation of corrosive water and S222, preparation of test sample; the S222, preparation of test sample comprises S1111, preparation of engine coolant concentrate sample; S2222, preparation of engine coolant sample; S3333, preparation of coolant sample containing potassium fluoroaluminate.

2. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 1, characterized in that: The preparation of the S11 specimen includes S11-1, the specimen is polished with No. 150, No. 180 and No. 240 emery cloth or sandpaper in turn, and then polished with metallographic sandpaper; S11-2, the specimen is first washed with warm water, then rinsed with distilled water, and finally rinsed with anhydrous ethanol; S11-3, the specimen is placed in a vacuum drying oven at 65-90°C and dried for 4 hours, and then picked up with tweezers; S11-4, the picked up specimen is placed in a dryer and cooled to room temperature; S11-5, the specimen is weighed to 0.1 mg using an analytical balance.

3. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 1, characterized in that: The preparation of S111 and corrosive water is to dissolve 220 mg of sodium chloride in 1 L of distilled water.

4. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 3, characterized in that: The preparation of the engine coolant concentrate sample in S1111 is to mix 1 volume of the engine coolant concentrate sample with 3 volumes of prepared corrosive water to make a 25% aqueous solution sample.

5. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 3, characterized in that: The preparation of the S2222 engine coolant sample is to dilute the coolant with the prepared corrosive water to a 25% aqueous solution sample.

6. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 1, characterized in that: The S3333 described above is a method of preparing a coolant sample containing potassium fluoroaluminate by adding potassium fluoroaluminate to a coolant sample with a total volume of 1 L.

7. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 1, characterized in that: The S2 test steps include the following steps: first, thoroughly clean the components used in the heat transfer corrosion chamber; second, use a new O-shaped rubber seal ring, and add a small amount of sample into the O-shaped groove before the O-shaped rubber seal ring is inserted; third, add 500L of sample into the heat transfer corrosion chamber through the air inlet, install an air filling pipe, install a safety cover, and gradually pressurize the heat transfer corrosion chamber to 140kPa with compressed air; turn on the heater, heat the specimen, and gradually adjust the pressure. When the temperature of the specimen reaches 135°C, the pressure in the heat transfer corrosion chamber is 190-200kPa; Step 4: Control the temperature of the specimen at 134-136℃, observe the temperature of the thermometer placed in the thermometer jack of the specimen at regular intervals, and continue the test at this temperature for one week; Step 5: At the end of the test, turn off the heater, wait for the heat transfer corrosion chamber to cool to room temperature, release the pressure in the heat transfer corrosion chamber, remove the air filling pipe, pour out or siphon out the sample, disassemble the heat transfer corrosion chamber, and take out the specimen; Step 6: Cleaning of the specimen: Wash the specimen with a soft brush and neutral detergent, and use the edge of a plastic scraper to remove the residue of the O-ring on the specimen; In the fume hood, soak the specimen in a mixture of chromium trioxide and phosphoric acid at 80℃ for 5 minutes, and brush the surface of the specimen with a soft brush from time to time; Then put the specimen on the Transfer the beaker of cleaning solution to an ultrasonic cleaner and clean for 1 min; remove the test piece from the cleaning solution, rinse with tap water, then with distilled water, and finally with anhydrous ethanol; check the surface of the test piece with a microscope, and if there is any residue, continue to clean it repeatedly; after cleaning, dry the test piece in a vacuum drying oven; use tweezers to pick up the test piece and put it in a dryer to cool to room temperature, and then weigh it to 0.1 mg; determine the blank cleaning mass loss value: take three test pieces prepared in step S22 and weigh them to 0.1 mg, then clean them according to the cleaning of the sixth step and weigh them to 0.1 mg, and take the average cleaning mass loss value of the three test pieces as the blank cleaning mass loss value.

8. The method for identifying the heat transfer corrosion resistance of antifreeze fluid to aluminum alloy according to claim 1, characterized in that: The S3 is calculated as the heat transfer corrosion rate R (mg / cm 2 ) is calculated according to the following formula: Where: m1-mass of the specimen before the test, g; m2-mass of the specimen after the test, g; B-mass loss value of the blank cleaning of the specimen, g; A-heat transfer surface area of ​​the specimen in the O-ring, cm 3 .